2005
DOI: 10.1007/s00424-005-1502-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of K–Cl cotransport by protein phosphatase 1α in mouse erythrocytes

Abstract: The K-Cl cotransport (KCC) is an electroneutral-gradient-driven-membrane transport system, which is involved in regulation of red cell volume. Although the regulatory cascade of KCC is largely unknown, a signaling pathway involving phosphatases and kinases has been proposed. Here, we investigated the expression and the activity of protein phosphatase 1(PP-1) isoforms in mouse red cells, focusing on two models of abnormally activated KCC: mice genetically lacking the two Src-family tyrosine kinases, Hck and Fgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Otherwise, these proteins showed reduced Tyr phosphorylation in PP1/PP2-treated ChAc RBCs, suggesting that Lyn might be also part of other signaling pathways involving other kinases or play a role as downstream regulator of phosphatase(s) similarly to what we previously described in other RBC models. 31,32 …”
Section: Exogenous Lyn Phosphorylates Several Targets In Chac Rbc Memmentioning
confidence: 99%
“…Otherwise, these proteins showed reduced Tyr phosphorylation in PP1/PP2-treated ChAc RBCs, suggesting that Lyn might be also part of other signaling pathways involving other kinases or play a role as downstream regulator of phosphatase(s) similarly to what we previously described in other RBC models. 31,32 …”
Section: Exogenous Lyn Phosphorylates Several Targets In Chac Rbc Memmentioning
confidence: 99%
“…Prx2 might act as an antioxidant and atypical molecular chaperone targeting free heme to control severe oxidation [82,83,106]. Indeed, the beneficial Notably, reticulocytes dismissed from the BM still express SFKs such as Lyn, Fyn, Fgr, or HcK as well as Syk, a Src related kinase [5,6,10,19]. In diseased red cells such as SCD, kinases such as Erk1/2 have been reported to contribute to adhesive events between red cells and inflammatory activated vascular endothelial surface [103,104].…”
Section: Antioxidant System(s) and Stress Erythropoiesismentioning
confidence: 99%
“…In addition, ROS might promote the transient oxidation of cysteine groups on proteins involved in signaling networks, contributing to protein conformational changes and affecting cell signaling. This results in either a block of protein function such as in protein tyrosine phosphatase (PTP) or protein phosphatase 1 and 2 (PP1, PP2A), or activation of protein kinases such as Src family kinases (SFKs) [3][4][5]. Furthermore, oxidation might directly induce/modulate kinase activity such as in Src family kinases (SFKs) or Akt serine-threonine kinase [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…12 In a variety of cell types it has been shown that the activity of KCC and NKCC are reciprocally regulated through changes in their phosphorylation status with phosphorylation activating NKCC and inactivating KCC. [13][14][15][16][17] Recently, the kinases and phosphatases responsible for modulating the KCC and NKCC phosphorylation status have been identified. The key kinases include selected members of the with-no lysine kinase family (WNK 1, 3 and 4), the STE20-related proline alanine-rich kinase (SPAK, or the rat homologue PASK) and the oxidative stress response kinase 1 (OSR1).…”
mentioning
confidence: 99%
“…32 In contrast, the protein phosphatases, PP1 and PP2A, have been shown to directly dephosphorylate NKCC and KCC leading to inactivation of NKCC [34][35][36][37] and activation of KCC. 17,31,[38][39][40] PP1 can also indirectly affect the NKCC/KCC phosphorylation by inhibiting SPAK. 27,35 While the phosphatases PP1 and PP2A are known to be actively expressed in rodent and human lenses, [41][42][43][44] less is known about the regulatory kinases.…”
mentioning
confidence: 99%